"DNA Evidence and the Islamic Law of Paternity in Light of Maqāṣid al‐Sharīʿa". (26th September 2022) - Fadel, Mohammad
Abstract: The protection of progeny ( nasl ) is one of the five universal ends ( al‐maqāṣid al‐kulliyya al‐khams ) of Islamic law. Despite this principle, classical Islamic law ( fiqh ), with very limited exceptions, barred affiliating a child conceived through illicit intercourse to the child's biological father, even if his identity was known. Was this based on a pragmatic recognition of the impossibility of identifying the "true" biological father of any child or a commitment to a deeper principle? If the former, the reliability of DNA testing would require a change in the rule, but if the latter, DNA's reliability would be irrelevant. Using primarily examples drawn from the Mālikī school of law, this paper argues, based on a purposive reading of those rules, that biological paternity, while important to Islamic law's juridical conception of paternity, was not always the most important legal value at stake. Rather, preserving a child's presumptive affiliation to the mother's legitimate sexual partner was also a crucial legal value that could carry greater weight than biological paternity when the two conflicted. The tendency to entrench the biological mother's legitimate sexual partner as the child's lawful father in all but the most obvious cases of adulterous conception suggests that for pre‐modern Islamic law, the best interests of the child weighed heavily in the law of paternity. In modern circumstances, therefore, DNA evidence of biological paternity, while it should be admissible to establish paternity of illegitimate children born to unmarried women, should not be admissible in cases involving children born to married women. Muslim states could also use DNA evidence of paternity to establish the monetary responsibility of adulterous fathers for their illegitimate children while denying them the benefits of legal paternity. Muslim states, in recognition of the importance of the well‐being of the child, might also reconsider their laws on adoption, by introducing distinctions between adoptive parents and children, on the one hand, and parents and children related by nasab, on the other hand.